The legal status of women - Гасанзаде, Саида Бахрам кизи (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
To define the woman, as one of the important social group in the society, is very difficult matter without completed researches as social and biological being. Despite the fact that woman are on the focus by the system of the international laws, and most researchers, it has not been defined as much enough as the scientific community and all need to recognize the definition of notion of «woman». The status of woman is also determined by the author and some other matters investigated.